Perancangan Website Pembelajaran Bahasa Jepang dengan Fokus Materi Klausa melalui Metode Waterfall - Dimas Ardiansyah; Ade Irma Purnamasari (Jurnal Informatika Terpadu, 2024)
Interest in Japanese is increasing in Indonesia, especially at LPK IHMI Cirebon, along with the growth of bilateral relations and information technology. This research aims to improve Japanese language learning, especially Japanese clause material through website design at LPK IHMI Cirebon. Conventional methods that are less interactive become obstacles to active participation of students. An innovative approach is proposed by utilizing a website, especially through the WordPress platform, and referring to the book "Minna no Nihongo" as a source of comprehensive learning material. The choice of WordPress platform is based on ease of use and integration with other services. LPK IHMI Cirebon faces the challenge of learning resources and conventional methods that are less interactive, impacting student participation, progress, motivation and understanding. The Waterfall research method was used with a focus on developing web learning modules, especially in chapter 22 "Minna no Nihongo" regarding Japanese clause material which is still considered the most difficult material in Japanese. Implementation involves the integration of learning technologies, especially Artificial Intelligence, to increase interactivity. The test results show that the website works as planned with an appropriate effectiveness level of 100% and provides positive performance as a Japanese language learning tool of 95%.